MENGEMBANGKAN INSTRUMEN NON TES: OBSERVASI, SKALA SIKAP, DAN WAWANCARA - Salsabila Harahap; Khoirul Bariah Rambe; Mariam Nasution (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Non-test instruments are evaluation tools in learning that aim to assess the affective and psychomotor domains of students comprehensively. This article discusses three main types of non-test instruments: observation, attitude scale, and interview. Observation is conducted through direct systematic observation of students’ behavior and activities during the learning process. The attitude scale is used to measure students’ attitudes, perceptions, motivations, and characters through a series of structured statements. Meanwhile, interviews are carried out through direct question-and-answer sessions to obtain in-depth information about students’ learning experiences and needs. Each instrument has its own purposes, development steps, advantages, and disadvantages. The use of non-test instruments is crucial because not all aspects of student development can be measured through written tests. Therefore, teachers need to develop non-test instruments that are valid, reliable, and appropriate to students’ characteristics in order to achieve a comprehensive and meaningful evaluation process.